Vascular sympathetic neurotransmission and its serotonergic regulation are modified by chronic fluoxetine treatment - José Ángel García-Pedraza; Cristina López; Juan Francisco Fernández-González; María Luisa Martín; Asunción Morán; Mónica García-Domingo (Elsevier, 2021)
Given the interconnection between depressive and cardiovascular disorders, we investigated whether antidepressant treatment (fluoxetine) modifies the serotonergic influence on rat vascular noradrenergic outflow. Twelve-week-old male Wistar rats received fluoxetine treatment (10 mg/kg/day; p.o.) for 14 days; then, they were pithed and prepared for sympathetic stimulation. Vasopressor responses were obtained by electrical stimulation of the sympathetic outflow (0.1, 0.5, 1, and 5 Hz) or i.v. noradrenaline (NA; 0.01, 0.05, 0.1, and 0.5 μg/kg). In fluoxetine-treated group, the electrical-induced vasoconstrictions were lower compared to non-treated rats. Intravenous infusion of 5-HT (10 μg/kg/min) inhibited the sympathetically-induced vasoconstrictions. Only 5-CT, 8-OH-DPAT and L-694,247 (5-HT1/7, 5-HT1A and 5-HT1D agonists, respectively) mimicked 5-HT-induced inhibition, while α-methyl-5-HT (5-HT2 agonist) increased the vasopressor responses. The inhibitory effect of 5-HT was: a) no modified by SB269970 (5-HT7 antagonist); b) abolished by WAY-100,635 (5-HT1A antagonist) plus LY310762 (5-HT1D antagonist); and c) potentiated by ritanserin (5-HT2A receptor antagonist). The vasoconstrictions induced by exogenous NA were not modified by 5-CT but were increased by α-methyl-5-HT. Our results suggest that fluoxetine treatment decreases NA release at vascular level and changes 5-HT modulation on rat vascular noradrenergic neurotransmission, inducing sympatho-inhibition via prejunctional 5-HT1A/1D receptors, and sympatho-potentiation via pre and/or postjunctional 5-HT2A receptors.